2020
DOI: 10.1002/cam4.2901
|View full text |Cite
|
Sign up to set email alerts
|

Management and risk factors of recurrent gestational trophoblastic neoplasia: An update from 2004 to 2017

Abstract: Objective We investigated the clinical characteristics, treatments, and survival of patients with gestational trophoblastic neoplasia (GTN) who experienced recurrence. Factors predictive of recurrence were also investigated. Methods Patients with GTN who recurred after completing chemotherapy at Peking Union Medical College Hospital Trophoblastic Disease Center were identified between January 2004 and December 2017. Logistic regression analysis was used to identify factors predictive of GTN recurrence. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(49 reference statements)
2
11
2
2
Order By: Relevance
“…As such, patients who are resistant to FAEV still have the option of switching to EMA/CO. Six of our patients (2.9%) relapsed after completing treatment; this was consistent with the relapse rate of 2.7% in our previous study of 1,250 patients with GTN who received primary treatment at our center [25] and lower than that of patients treated with EMA/CO (3% to 16.4%) [7,10,[12][13][14]. Further clinical trials should be performed to compare FAEV with EMA/CO.…”
Section: Discussionsupporting
confidence: 92%
“…As such, patients who are resistant to FAEV still have the option of switching to EMA/CO. Six of our patients (2.9%) relapsed after completing treatment; this was consistent with the relapse rate of 2.7% in our previous study of 1,250 patients with GTN who received primary treatment at our center [25] and lower than that of patients treated with EMA/CO (3% to 16.4%) [7,10,[12][13][14]. Further clinical trials should be performed to compare FAEV with EMA/CO.…”
Section: Discussionsupporting
confidence: 92%
“…In the Yang study, in contrast to the present study, the median duration of recurrence was reported, whereas, in our study, the meantime was reported. Besides, similar to the present study in the Yang study, it was shown that more than 78% of patients had recurrence within one year after treatment, and 10% had recurrence after two years (Kong, Zong, Cheng, Jiang, Wan, Feng, Ren, Zhao, Yang, & Xiang, 2020). These findings indicate the need for long term monitoring of bHcg levels after complete recovery.…”
Section: Discussionsupporting
confidence: 90%
“…Yang et al In a study of 1130, patients have reported the 314 patients with recurrent GTN (3.4%), which was similar to the results obtained in this study (Yang, Xiang, Wan, & Yang, 2006). However, another study by the same group found a 6.5% recurrence GTN rate between, which was much more than our study findings (Kong, Zong, Cheng, Jiang, Wan, Feng, Ren, Zhao, Yang, & Xiang, 2020). Also, Barga et al, In a study on GTN, followed molar pregnancy, showed that 10 of 2284 GTN patients would relapse (Braga, Maestá, Matos, Elias, Rizzo, & Viggiano, 2015).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In all, 23 patients with cervical GTN underwent a prognostic analysis, among whom three relapsed 4-6 months after their last chemotherapy session. The recurrence rate was 13%, which was higher than that in a review of 1827 patients with GTN who achieved CR at our center, 118 (6.5%) of whom experienced recurrence during follow-up [27]. Notably, two of the three patients who relapsed in the study had not undergone hysterectomy, with the site of recurrence being the cervix.…”
Section: Discussioncontrasting
confidence: 56%